Intervensi Nutrisi Neuroprotektif terhadap Kadar GFAP dan Skor NIHSS pada Pasien Stroke Iskemik - Diah Retno Wahyuningrum; Kalasta Ayunda Putri; Fitni Hidayati; Fathia Rahmadini (Pusat riset dan Inovasi Nasional, 2025)
Stroke is one of the leading causes of disability and mortality worldwide, with significant neurological and biochemical consequences. This study aimed to examine the effect of a neuroprotective nutritional intervention consisting of protein, phosphatidylcholine, phosphatidylserine, and inulin on glial fibrillary acidic protein (GFAP) levels and National Institutes of Health Stroke Scale (NIHSS) scores in acute ischemic stroke patients. The study employed a quasi-experimental design with a pretest-posttest control group, involving 18 patients divided equally into intervention and control groups. Data were collected at Dr. Kariadi General Hospital Semarang from January to February 2020, measuring serum GFAP levels using ELISA and assessing NIHSS scores before and after a seven-day intervention. The intervention group showed a significant decrease in GFAP levels and a more pronounced improvement in NIHSS scores compared to the control group. These findings suggest that the neuroprotective nutritional intervention may support both biochemical and clinical recovery in acute ischemic stroke patients. Implementing such nutritional strategies could complement standard care and enhance rehabilitation outcomes. Further research with larger sample sizes and longer follow-up is recommended to confirm these results and optimize the intervention protocol.